Exposure Assessment of Trans-Fatty Acids through Consumption of Sour Cream in Yerevan - Pipoyan, D. A.; Beglaryan, M. R.; Stepanyan, S. A. (ՀԱԱՀ հիմնադրամ)
The aim of the study is to assess the content of trans-fatty acids (TFA) present in the sour cream produced in the RA and conduct a dietary exposure assessment. Data on sour cream consumption has been gathered through food frequency questionnaire (FFQ). TFA contents in sour cream samples were determined using the method of gas chromatography. Daily intake of TFA through sour cream consumption has been estimated. TFA daily intake (E %) accounted for 0.03 %, 0.185 % and 0.457 % of total energy intake (kcal) for sour cream consumption Cluster 1, 2 and 3, respectively. It was discovered that TFA daily intake through sour cream consumption does not exceed the recommended threshold value (≤ 1 E %).
Keywords: Food Science and Technology